2012
DOI: 10.1002/pds.3266
|View full text |Cite
|
Sign up to set email alerts
|

High use of tramadol in Germany: an analysis of statutory health insurance data

Abstract: Despite some limitations, this study shows the prescriptions of tramadol in Germany in an authentic way. It seems that there are some 'challenging' patients that present a treatment dilemma for some prescribers. This might result in a high use of tramadol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(69 reference statements)
1
11
0
Order By: Relevance
“…These restrictions were so far limited to pediatric settings, but they questioned the status of codeine as the 'number one opioid' in the UK. In Germany, the most frequent opioids were tramadol (43.41%), tilidine (24.78%) and codeine (19.99%), confirming the results from another published study showing that tramadol remains one of the most prescribed analgesics for noncancer pain in Germany, despite some controversial discussions regarding the use of step II opioids in noncancer patients (see Table 4) [18].…”
Section: Discussionsupporting
confidence: 75%
“…These restrictions were so far limited to pediatric settings, but they questioned the status of codeine as the 'number one opioid' in the UK. In Germany, the most frequent opioids were tramadol (43.41%), tilidine (24.78%) and codeine (19.99%), confirming the results from another published study showing that tramadol remains one of the most prescribed analgesics for noncancer pain in Germany, despite some controversial discussions regarding the use of step II opioids in noncancer patients (see Table 4) [18].…”
Section: Discussionsupporting
confidence: 75%
“…In the UK, higher doses and prolonged use of strong opioids were related to increasing demands for pain relief in CNCP . In addition, a cross‐sectional study conducted in Germany found that higher tramadol utilisation was associated with CNCP diagnosis . However, similar to other opioids, there is currently no robust evidence to support the clinical effectiveness of prolonged tramadol utilisation for CNCP .…”
Section: Discussionmentioning
confidence: 99%
“…Tramadol is indicated for moderate to severe pain in the United Kingdom (UK). In the past decade, the utilisation of tramadol has consistently increased in many countries, including the United States (US), Germany, and the UK . According to the UK National Health Service (NHS) Business Services Authority, the annual tramadol utilisation in England increased from 5.9 to 11.1 million defined daily doses (DDDs) between 2005 and 2012; coincidently, there was a marked increase in the number of tramadol‐related deaths during the same period.…”
Section: Introductionmentioning
confidence: 99%
“…They developed 9 types of pain to which 77.1% of all patients with at least two opioid prescriptions within a one year period could be allocated. By aggregating these 9 pain types and further including unspecific diagnoses, nearly all persons with at least one prescription of tramadol (91.7%) could be identified as patients with pain in a recent analysis [23]. Based on these studies we used the following pain types and ICD-10 diagnoses:…”
Section: Methodsmentioning
confidence: 99%